Early postoperative results of on-pump coronary endarterectomy: is it still a controversy? - Eriş, Cüneyt; Sanrı, Umut Serhat; Engin, Mesut; Yavuz, Senol (The European Research Journal, 2021)
Objectives: The coronary endarterectomy combined with coronary artery bypass grafting (CABG) is an useful but still controversial surgical technique in diffuse coronary artery disease. The aim of this study was to analyze the operative and early postoperative outcomes of the patients who underwent CABG with and without coronary endarterectomy. Methods: This retrospective study included a total of 312 consequtive patients undergoing on-pump CABG from December 2018 to December 2020 in the Department of Cardiovascular Surgery, Bursa Yüksek İhtisas Training and Research Hospital. Patients were divided into 2 groups as those who underwent coronary endarterectomy combined with on-pump CABG (Group 1, n = 48) and those who underwent isolated on-pump CABG (Group 2, n = 264). Peroperative variables were obtained from our hospital's computerized database and retrospectively analyzed. Results: Previous percutaneus coronary intervention rate and the number of patients with diabetes mellitus was significantly higher in the endarterectomy group. The demographics and characteristics of the patients were similar between the two groups. The median number of distal anastomoses was 4 (2-5) in Group 1 and 2 (1-5) in Group 2. Median cross-clamp duration and perfusion times in Group 1 were longer than Group 2 (82 min vs. 63 min; p < 0.001 and 120 min vs. 95 min; p = 0.003, respectively). A total of 54 coronary endarterectomy practices were performed on 48 patients, and the LAD artery (73%) was the most endarterectomized vessel. In Group 1, postoperative 24 hours high-sensitive troponin I levels were significantly higher than in Group 2 (p < 0.001). There was no significant difference between the groups in terms of operative mortality, low cardiac output rates and perioperative myocardial infarction rates. Postoperative atrial fibrillation was significantly higher in Group 1 (p = 0.023). Conclusions: Although coronary endarterectomy is a complex procedure, in patients with diffuse coronary artery disease, it is an essential and sometimes mandotary method in order to achieve complete revacularization and can be performed safely with acceptable operative and early postoperative outcomes.